MOISTURE INDUCED DEFORMATIONS IN GLULAM MEMBERS - EXPERIMENTS AND 3-D FINITE ELEMENT MODEL - Kiwelu, Henry M. (Tanzania Journal of Engineering and Technology, 2018)
Experiments were performed on scaled glue laminated bending specimens to observe time dependent development of deformations during drying and wetting. Measurements determined changes in the average moisture content and external shape and dimensions between when specimens were placed into constant or variable climates. Alterations in the external shape and dimensions reflected changes in the average value and distribution of moisture and mechanosorptive creep in the glulam. The results are being used to develop a sequentially-coupled three-dimensional hygrothermal Finite Element (FE) model for predicting temporally varying internal strains and external deformations of drying or wetting solid wood structural components. The model implies temporally varying, and eventual steady, state internal stress distributions in members based on elastic and creep compliances that represent wood within glulam as a continuous orthotropic homogenised material. Thus, predictions are consistent with smeared engineering stress analysis methods rather than being a physically correct analogue of how solid wood behaves. This paper discusses limitations of and intended improvements to the FE modelling. Complementary investigations are underway to address other aspects of the hygrothermal behaviour of structural members of wood and other materials (e.g. reinforced concrete) embedded within superstructure frameworks of multi-storey hybrid buildings.